Culture and Sustainable Development in the City Urban Spaces of Possibilities - Kagan, Sacha (Routledge Research in Planning and Urban Design, 2023)
This book exposes the potential to advance a cultural approach to sustainable urban development. It explores urban "spaces of possibilities" and links them to the seized or missed opportunities for innovative forms of transversal partnerships throughout the city and of culturally sensitive urban policies. The call for sustainability brings with it challenges for which, in view of the urgency of social transformation, institutional innovations are necessary. Sustainable urban development will only succeed through creative impulses, experiments, trying out innovative ideas, making alternatives visible, in particular through locally rooted urban initiatives, artistic actions and social movements. Discussing many concrete examples from several years of empirical research in the cities of Hanover and Hamburg (Germany), Baltimore and Chicago (USA), Bangalore (India), St. Petersburg (Russia), Singapore, and Vancouver (Canada), the book connects urban spaces and their actors, looks at their guiding principles, strategies and concrete practices, and identifies new levers, networks and alliances. Readers will find in this book not only inspiring examples of culture in everyday life in the city, but also explanations about the qualities that make local cultural initiatives especially full of potentials, and how they may translate into city-wide changes, engaging with the whole City as Space of Possibilities. The book will interest researchers and advanced students in the interdisciplinary fields of urban studies, sustainability science / sustainability research, cultural sciences, urban sociology, sociology of the arts/cultural sociology; and those interested in the transdisciplinary collaborations between the arts, academia and civil society.